Targeting of BCL2 Family Proteins with ABT-199 and Homoharringtonine Reveals BCL2- and MCL1-Dependent Subgroups of Diffuse Large B-Cell Lymphoma - Klanova, Magdalena; Andera, Ladislav; Brazina, Jan; Svadlenka, Jan; Benesova, Simona; Soukup, Jan; Prukova, Dana; Vejmelkova, Dana; Jaksa, Radek; Helman, Karel; Vockova, Petra; Lateckova, Lucie; et al. (Clinical cancer research, 2016)
PURPOSE: To investigate the roles of BCL2, MCL1, and BCL-XL in the survival of diffuse large B-cell lymphoma (DLBCL). EXPERIMENTAL DESIGNS: Immunohistochemical analysis of 105 primary DLBCL samples, and Western blot analysis of 18 DLBCL cell lines for the expression of BCL2, MCL1, and BCL-XL. Pharmacologic targeting of BCL2, MCL1, and BCL-XL with ABT-199, homoharringtonine (HHT), and ABT-737. Analysis of DLBCL clones with manipulated expressions of BCL2, MCL1, and BCL-XL. Immunoprecipitation of MCL1 complexes in selected DLBCL cell lines. Experimental therapy aimed at inhibition of BCL2 and MCL1 using ABT-199 and HHT, single agent, or in combination, in vitro and in vivo on primary cell-based murine xenograft models of DLBCL. RESULTS: By the pharmacologic targeting of BCL2, MCL1, and BCL-XL, we demonstrated that DLBCL can be divided into BCL2-dependent and MCL1-dependent subgroups with a less pronounced role left for BCL-XL. Derived DLBCL clones with manipulated expressions of BCL2, MCL1, and BCL-XL, as well as the immunoprecipitation experiments, which analyzed MCL1 protein complexes, confirmed these findings at the molecular level. We demonstrated that concurrent inhibition of BCL2 and MCL1 with ABT-199 and HHT induced significant synthetic lethality in most BCL2-expressing DLBCL cell lines. The marked cytotoxic synergy between ABT-199 and HHT was also confirmed in vivo using primary cell-based murine xenograft models of DLBCL. CONCLUSIONS: As homoharringtonine is a clinically approved antileukemia drug, and ABT-199 is in advanced phases of diverse clinical trials, our data might have direct implications for novel concepts of early clinical trials in patients with aggressive DLBCL.
Keywords: Bridged Bicyclo Compounds, Heterocyclic; nitrofenoly; bicyklické sloučeniny heterocyklické; regulace genové exprese u nádorů; Humans; protein bcl-X; sulfonamidy; Biphenyl Compounds; bifenylové sloučeniny; lidé; protein MCL-1; zvířata; proliferace buněk; myši; Proto-Oncogene Proteins c-bcl-2; bcl-X Protein; Mice; apoptóza; xenogenní modely - testy protinádorové aktivity; difúzní velkobuněčný B-lymfom; Cell Proliferation; Nitrophenols; piperaziny; Harringtonines; Lymphoma, Large B-Cell, Diffuse; nádorové buněčné linie; Xenograft Model Antitumor Assays; Piperazines; Myeloid Cell Leukemia Sequence 1 Protein; Animals; Cell Line, Tumor; Gene Expression Regulation, Neoplastic; harringtoniny; protoonkogenní proteiny c-bcl-2; Apoptosis; Sulfonamides